Discontinuous epidemic transition due to limited testing - Davide Scarselli (Nature Portfolio, 2021)
Common mitigation measures gradually inhibit the spread of infectious diseases, yielding smooth transitions to large-scale epidemics. As Scarselli et al. show, limited testing may radically change the transition to include jumps, potentially resulting in unforseen, accelerated growth of case numbers.